Prediction of punching behaviour of RC slabs using continuum non-linear FE analysis. (15th October 2016) - Shu, Jiangpeng; Plos, Mario; Zandi, Kamyab; Johansson, Morgan; Nilenius, Filip
Highlights: A NLFEA method for slabs subjected to punching failure is developed. Punching behaviour of RC slabs can be reflected in NLFEA. Critical shear crack can be reflected by using 3D NLFEA. NLFEA of two-way RC slab is significantly affected by modelling parameters. Influence of size effects and flexural reinforcement can be reflected in NLFEA. Abstract: Failure of reinforced concrete (RC) slabs without shear reinforcement in punching has been a challenging problem for nonlinear finite element (FE) analysis. To improve the analysis approach, this study was conducted by developing a nonlinear FE analysis method for slabs subjected to punching failure without shear reinforcement, using three-dimensional continuum elements. The influence of several modelling choices were investigated by comparing such results as loadcarrying capacity, load-deflection response and crack pattern from the FE analyses with available experimental data. The proposed method shows the possibility of accurately predicting the load-carrying capacity and realistically describing the behaviour of slabs.